The moral case for fossil fuels - Epstein, Alex, 1980- (Portfolio/Penguin, 2014)
The author believes that "we're taught to think only of the negatives of fossil fuels, their risks and side effects, but not their positives--their unique ability to provide cheap, reliable energy for a world of seven billion people. And the moral significance of cheap, reliable energy, Epstein argues, is woefully underrated. Energy is our ability to improve every single aspect of life, whether economic or environmental"--Amazon.com.